Hubungan Media Massa terhadap Human Resources dan Hardware (Studi Literature) - Maharani, Amalina (Siber Nusantara Publisher, 2023)
Abstract: The Literature Review article on the Relations of Mass Media to Human Resources and Hardware is a scientific article that aims to build a research hypothesis on the influence of variables to be used in further research, within the scope of Human Resource Management. The method of writing literature review articles is the library research method, which is sourced from online media such as Google Scholar, Mendeley, and other academic online media. The results of this study are: 1) Mass Media relates to Human Resources; 2) Mass Media relates to Hardware; and 3) Human Resources related to Hardware. Apart from the exogenous variables that influence the endogenous variables, there are other factors including: Electronic Media, Digital Media and Education. Abstrak: Artikel Literature Review Hubungan Media Massa terhadap Human Resources dan Hardware merupakan artikel ilmiah yang bertujuan membangun hipotesis riset pengaruh antar variabel yang akan digunakan dalam riset selanjutnya, dalam ruang lingkup ilmu Manajemen Sumber Daya Manusia. Metode penulisan artikel literature review yaitu dengan metode library research, yang bersumber dari media online seperti Google Scholar, Mendeley, dan media online akademik lainnya. Hasil dari penelitian ini yaitu: 1) Media Massa berhubungan terhadap Human Resources; 2) Media Massa berhubungan terhadap Hardware; dan 3) Human Resources berhubungan terhadap Hardware. Selain dari variabel exogen yang mempengaruhi variabel endogen, terdapat faktor lain diantaranya meliputi: Media Elektronik, Media Digital dan Pendidikan.